Human scattered tubular cells represent a heterogeneous population of glycolytic dedifferentiated proximal tubule cells. Issue 2 (19th December 2022) - Eymael, Jennifer; van den Broek, Martijn; Miesen, Laura; Monge, Valerie Villacorta; van den Berge, Bartholomeus T; Mooren, Fieke; Velez, Vicky Luna; Dijkstra, Jelmer; Hermsen, Meyke; Bándi, Péter; Vermeulen, Michiel; de Wildt, Saskia; et al.
Abstract: Scattered tubular cells (STCs) are a phenotypically distinct cell population in the proximal tubule that increase in number after acute kidney injury. We aimed to characterize the human STC population. Three‐dimensional human tissue analysis revealed that STCs are preferentially located within inner bends of the tubule and are barely present in young kidney tissue (<2 years), and their number increases with age. Increased STC numbers were associated with acute tubular injury (kidney injury molecule 1) and interstitial fibrosis (alpha smooth muscle actin). Isolated CD13 + CD24 − CD133 − proximal tubule epithelial cells (PTECs) and CD13 + CD24+ and CD13 + CD133 + STCs were analyzed using RNA sequencing. Transcriptome analysis revealed an upregulation of nuclear factor κB, tumor necrosis factor alpha, and inflammatory pathways in STCs, whereas metabolism, especially the tricarboxylic acid cycle and oxidative phosphorylation, was downregulated, without showing signs of cellular senescence. Using immunostaining and a publicly available single‐cell sequencing database of human kidneys, we demonstrate that STCs represent a heterogeneous population in a transient state. In conclusion, STCs are dedifferentiated PTECs showing a metabolic shift toward glycolysis, which could facilitate cellular survival after kidney injury. © 2022 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of The Pathological Society of Great Britain and Ireland.